Clinical and molecular characteristics of a novel rare de novo variant in PPP2CA in a patient with a developmental disorder, autism, and epilepsy - Verbinnen, Iris; Procknow, Sara S.; Lenaerts, Lisa; Reynhout, Sara; Mehregan, Aujan; Ulens, Chris; Janssens, Veerle; King, Katherine A. (Frontiers in Cell and Developmental Biology, 2022)
PP2A-related (neuro)developmental disorders are a family of genetic diseases caused by a heterozygous alteration in one of several genes encoding a subunit of type 2A protein phosphatases. Reported affected genes, so far, are PPP2R5D, encoding the PP2A regulatory B56δ subunit; PPP2R1A, encoding the scaffolding Aα subunit; and PPP2CA, encoding the catalytic Cα subunit – in that order of frequency. Patients with a pathogenic de novo mutation in one of these genes, in part present with overlapping features, such as generalized hypotonia, intellectual and developmental delay, facial dysmorphologies, seizures and autistic features; in part with opposite features, e.g. smaller versus larger head sizes, or normal versus absent corpus callosum. Molecular variant characterization has been consistent so far with loss-of-function or dominant-negative disease mechanisms for all three affected genes. Here, we present a case report of another PPP2CA-affected individual, with a novel de novo missense variant, resulting in a one-amino acid substitution in the Cα subunit: p.Cys196Arg. Biochemical characterization of the variant revealed its pathogenicity, as it appeared severely catalytically impaired, showed mildly affected A subunit binding, and moderately decreased binding to B/B55, B”/PR72 and all B56 subunits, except B56γ1. Carboxyterminal methylation appeared unaffected, as was binding to B”’/STRN3 – all being consistent with a partial loss-of-function. Clinically, the girl presented with mild to moderate developmental delay, a full scale IQ of 83, mild dysmorphic facial features, tonic-clonic seizures, and autistic behaviors. Brain MRI appeared normal. We conclude that this individual falls within the milder end of the clinical and molecular spectrum of previously reported PPP2CA cases.